1976
DOI: 10.1136/jnnp.39.7.674
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous silent period in masseter muscles: a clinical and electrodiagnostic evaluation.

Abstract: SYNOPSIS In 35 normal subjects electromyographic silent periods were constantly evoked bilaterally in the masseter muscles during maximal contraction after unilateral electrical stimulation over the infraorbital or mental nerve. Findings in this study and data obtained in 30 patients suffering from trigeminal (26) and facial (four) nerve lesions suggest that the silent period evoked according to our methods is cutaneous in origin. The trigeminal sensory root forms the afferent limb of the silent period reflex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This study together with our previous findings (23) indicated that both the appearance and magnitude of RMS‐EMG values in the 400–500 ms following 450 ms train stimuli may not be directly linked to pain and may not be affected by the location of the stimulation in the oro‐facial areas used in this study. This is particularly likely to happen if a long‐duration pulse is used (10); if a train of high frequency and short‐duration pulses are delivered, the reflex threshold decreases, falling below the pain threshold. This is in accordance with our previous study (22), when non‐painful ultra‐long (450 ms pulse train) stimuli were used in settings for the contingent electrical stimulation applied to temporalis muscle to reduce the EMG activity during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…This study together with our previous findings (23) indicated that both the appearance and magnitude of RMS‐EMG values in the 400–500 ms following 450 ms train stimuli may not be directly linked to pain and may not be affected by the location of the stimulation in the oro‐facial areas used in this study. This is particularly likely to happen if a long‐duration pulse is used (10); if a train of high frequency and short‐duration pulses are delivered, the reflex threshold decreases, falling below the pain threshold. This is in accordance with our previous study (22), when non‐painful ultra‐long (450 ms pulse train) stimuli were used in settings for the contingent electrical stimulation applied to temporalis muscle to reduce the EMG activity during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Median nerve somatosensory evoked potentials (SSEPs) and brainstem auditory evoked responses (BAERs; Keypoint Classic; Medtronic, Skovlunde, Denmark) were recorded using previously established protocols. Small (Aδ) fiber involvement was assessed by measurement of the cutaneous silent period (CSP) in the upper and lower limbs bilaterally . We randomly chose left‐ or right‐sided data for the limb (non‐cranial region) studies in our analysis and tested both sides for confirmation that the abnormality was bilateral.…”
Section: Methodsmentioning
confidence: 99%
“…Trigeminal stimulation produces silent periods (SPs) in a variety of cranial muscles, as recently reviewed 2. The masseteric inhibitory reflex (MIR) refers to silent periods that occur bilaterally in the active masseter muscle following stimulation of the face, gums, or teeth 49. The MIR has certain similarities to CSPs in limb muscles.…”
Section: Topographic Distribution Of Cspsmentioning
confidence: 99%